Application of science and technology of analysis of big data to conserve geological heritages in trung khanh area, Cao Bang province - Trinh Ngoc Nhu Anh; Nguyen Quoc Phi; Phan Thi Mai Hoa; Nguyen Thi Mai Huong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Trung Khanh area, Cao Bang province is a place with geological and cultural heritages with many wonders and famous scenic spots. However, this is also one of the mountainous localities where environmental disasters often occur, especially landslides and flash floods, which are likely to affect the conservation of geological heritages in the area. The article analyzes information sources extracted from multi-temporal remote sensing images, topographical data, hydrometeorology, and other human activities,... in the study area using big data analysis methods. The analysis results using big data analysis methods show that the ANN artificial intelligence network model gives the best results with the global accuracy reaching 89.3%; followed by the support vector method (87.4%) and finally the decision tree model (83.6%). The results of mapping areas at risk of environmental hazards help identify geological heritage sites located in high-risk areas that need to be protected. The hazard zoning maps for environmental hazards are not only applicable to heritage sites in the study area but can also be applied to similar areas, towards the goal of sustainable management and development of natural resources that need to be conserved.